Aplicación de Lean Construction a través de la metodología Last Planner a proyectos de vivienda social de FUPROVI - Alpízar-Ávalos, Greivin de los Ángeles (Instituto Tecnológico de Costa Rica, 2017)
The present paper consists on the final report of the graduation project, which consisted on designing the procedure for the application of Last Planner System® (LPS) and perform a pilot application on a project under construction from the Housing Developer Foundation (FUPROVI for its acronym in Spanish). Last Planner System® is a methodology for planning, monitoring and control of construction projects, which is created product of the development of the Lean Construction philosophy, this allows to improve deadlines and costs. The main objective of the project was to optimize the planning, monitoring and control process of the FUPROVI’s construction works through the design of the application’s procedure. In order to complete this it was carried out a bibliographic investigation, the execution of the projects by the Foundation were studied and based on this analysis it was set the procedure for the LPS application. Among the most important results it was shown that the LPS application allows to determine the delay causes in the activities in aimed at its solution in order to execute improvements. The most important conclusion after the project was completed is that the three level planning that have the LPS application are essential to obtain a more fluid and constant workflow.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2017.
Keywords: Lean construction; Last planner; Programación; Seguimiento; Control